Human Resource Management Development in Islamic Educational Institutions [Pengembangan Manajemen Sumber Daya Manusia di Lembaga Pendidikan Islam] SD terpadu Nurul Hidayah Wamena Papua Pegunugnan - Moh Nor Fiqni; Ida Rindaningsih (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Educational institutions will easily achieve their goals with sufficient human resources. The purpose of this paper is to improve the understanding of the concept and procedures of human resource management development in Islamic educational institutions. The author uses a qualitative approach, which is in accordance with the type of library research. The author collects research materials, reads literature, makes short notes, and converts the information they read into research data. The analysis shows that planning, coordinating, implementing, and evaluating are activities included in human resource management development. Education, training, and self-development are part of the human resource management development process. To provide more details about the human resource development process, the first is by identifying needs; the second is by designing problems, programs, participation, and educational calendars.Design individual needs, design group needs, design time, procedures, and evaluation; then, the implementation process, and finally, the implementation of evaluation.